2016
DOI: 10.1177/1747954116667106
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the pressure on the teams batting or bowling in the second innings of limited overs cricket matches

Abstract: A team batting second in a limited overs match is under pressure to score the required number of runs for victory in the allotted number of overs without losing all its wickets. The bowling team has to prevent its opponents from reaching the target for victory. The objective of this study is to define methods that can be used to assess the pressure on the two teams' batsmen and bowlers when playing the second innings of a Twenty20 or One-day match, and also to define methods to determine the best partnership a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Pressure Index Bhattacharjee and Lemmer (2016) have forwarded the concept and formula of pressure index as a tool to analyse cricket data. According to them, the formula for pressure index is given by 2where T is the target runs to be scored by the team, and B is the total number of balls available to the team in any innings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pressure Index Bhattacharjee and Lemmer (2016) have forwarded the concept and formula of pressure index as a tool to analyse cricket data. According to them, the formula for pressure index is given by 2where T is the target runs to be scored by the team, and B is the total number of balls available to the team in any innings.…”
Section: Methodsmentioning
confidence: 99%
“…Bhattacharjee and Lemmer (2016) have forwarded the concept and formula of pressure index as a tool to analyse cricket data. According to them, the formula for pressure index is given by …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure of large target tempts the bat-second team to take additional risks that may negatively affect their natural batting performance. Even highly competitive teams have been found vulnerable to such high target pressure as their batting performance often collapses after scoring unusually low total while chasing a high target, 17 which is often termed as 'choking' or 'strangling' and has been studied by Lemmer. 18 All these phenomena do not guarantee a level playing field for both teams since the playing order may ultimately influence the outcome of the game.…”
Section: Proposed Researchmentioning
confidence: 99%
“…Given expected runs accounts for the batting teams scoring rate and resources remaining, the pressure metric adopts an assumption like that outlined in Bhattacharjee & Lemmer (2016). Bhattacharjee & Lemmer (2016) suggested that second innings pressure is a function of the remaining runs and required run rate to achieve the target total. This has been incorporated in the pressure metric, as runs remaining and required are embedded in the expected runs model.…”
Section: Pressure Modelmentioning
confidence: 99%